Characterisation of Viral Membrane Assembly Proteins A6 and A11 of Vaccinia Virus - Inam,Hadiqa (2025)
Poxviruses are large, double-stranded DNA viruses that replicate directly in the cytoplasm of the host eukaryotic cell. During assembly of viral particle progeny, viral membrane precursors derived from the endoplasmic reticulum, exhibit stabilised open ends inside intermediate structures called crescents. The process of viral membrane biogenesis during poxvirus assembly remains poorly understood. In particular, the key role of five essential Viral Membrane Assembly Proteins (VMAPs) remains enigmatic, including the contribution of A6 and A11 to the early stages of virion assembly, how they interact with one another and cell-derived membranes. This study aims at characterising A6 and A11 using a combination of biophysical and biochemical approaches to investigate their potential interaction and assess A11 interaction with lipids in vitro. We expressed and purified recombinant A6 and A11 using E. coli and wheat germ extract in cell-free expression systems, respectively. A6 was analysed by analytical ultracentrifugation, SEC-MALS, and mass photometry to study its oligomeric state. In parallel, the extent of A11 reconstitution in proteoliposomes was assessed by flotation assays. Finally, protein-protein interactions were examined using pull-down and western-blotting. For A6, there is a concentration-dependent shift from monomer to higher-order assemblies. While A11 appeared to be difficult to purify and unstable in solution, flotation assays suggested it may associate with liposomes under some conditions. First results of pull-down also showed a possible weak or transient interaction between A6 and A11. On one hand, A6 is a highly dynamic protein with multiple oligomeric states. On the other, A11 shows potential membrane-binding capacity and interaction with A6, though more work is required to confirm and further characterise these interactions.
Keywords: viral assembly; membrane remodelling; poxvirus; VMAPs; biochemistry